2012
DOI: 10.1093/jjco/hys036
|View full text |Cite
|
Sign up to set email alerts
|

Making the Decision for Home Hospice: Perspectives of Bereaved Japanese Families who had Loved Ones in Home Hospice

Abstract: Objective: The aim of the study was to evaluate whether family members believed that the decision for home hospice had been the acceptable choice and to identify factors related to families accepting that the decision was good. Methods: In June 2007, a cross-sectional anonymous questionnaire was distributed to bereaved family members of terminal cancer patients in Japan who died at home in the previous 6 months. The questionnaire included questions about whether the family member believed that the decision for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 44 publications
0
3
0
Order By: Relevance
“…Although the Japanese government promotes home care, home death from cancer represents 10.4% of the total deaths of cancer patients . Despite the psychological challenges associated with the end of life (eg, depression and anxiety) for patients and family members, cancer patients prefer to stay at home . This may represent a good death for a cancer patient.…”
Section: Introductionmentioning
confidence: 99%
“…Although the Japanese government promotes home care, home death from cancer represents 10.4% of the total deaths of cancer patients . Despite the psychological challenges associated with the end of life (eg, depression and anxiety) for patients and family members, cancer patients prefer to stay at home . This may represent a good death for a cancer patient.…”
Section: Introductionmentioning
confidence: 99%
“…[816212324] In cases where family members are involved in the decision-making about a place of death, patients made the decision when the disease conditions coincided with the [Awareness of the family about the disease condition and the place of death], such as <Understanding of the family about the disease condition>[24] and <Understanding of the family on a place of death>. [2431] It is reported that there is a tendency in cultures that patients have positive attitudes and determination[811] and that the family plays an important role in decision-making. [728] From this background, the [Intention of patients and family] for a place of death involves the following subcategories: <Attitudes toward the decision of patient and family>,[728] <Experience of care which patients received in the past>,[10182224] <Cultural and religious values of patients>,[710] <Thoughts of the family hoping to support the wishes of the patients>,[1021242930] and <Differences in the intentions of patients and family> related to the place of death and how the patient spends time till the end of life.…”
Section: Resultsmentioning
confidence: 99%
“…Of these, we selected 20 articles from among the identified articles by excluding 334 articles that had no descriptions about the decision-making about a place of death, six articles that focused on childhood cancer patients and their parents, three articles focusing on noncancer patients, and one article focusing on cancer patients with developmental disorders, 27 case study reports, and nine articles addressed at only medical professionals. Adding ten articles from a manual search using commonly known literature and cited articles to the twenty, we reviewed thirty articles[789101115161718192021222324252627282930313233343536373839] in total.…”
Section: Methodsmentioning
confidence: 99%